Two new species of the spider genus Wanniyala Huber & Benjamin, 2005 (Araneae: Pholcidae) from Sri Lanka - Xin, Yafei; Yao, Zhiyuan; Li, Shuqiang (Zootaxa, 2020)
Two new species of the spider genus Wanniyala Huber & Benjamin, 2005 are described from Sri Lanka: W. badulla sp. nov. (Uva Province; male and female) and W. batatota sp. nov. (Sabaragamuwa Province; male and female). In addition, new records of W. mudita Huber, 2019 (Western Province; male) and W. viharekele Huber, 2019 (Southern Province; male and female) are provided.